Strategi Lembaga Adat Panglima Laot dalam Menyelesaikan Konflik (Sengketa) Masyarakat Nelayan di Kabupaten Pidie Provinsi Aceh - Rachmad Munazir; Mujiburrahman Mujiburrahman (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
This study aims to investigate the role of Panglima laot in solving the conflicts amongst the fishermen in Aceh. Panglima Laot (The sea commander) is a tribal fishing community exist in Aceh that constitute and use customary maritime law (hukom adat laot) as their fundamental rule. Panglima laot has a strategic function as the only platform for all fishmernen in Aceh. One of their strategic duties is to manage the fisherman community as a unite coastal community that depends their life on the sea to meet their daily needs. Panglima laot also serves as the one who will take the responsibility to solve the social conflicts that may occur among the fishermen. This study used the qualitative descriptive method. The data was collected mainly from words and actions that were gathered from observation and and interview. This research tried to find out the concept map and strategy used by Panglima laot in solving various kinds of cases amongst the fishermen. The result showed that Panglima laot used the strategic customary approach to resolve the conflicts. Further, they put the custom values that has rooted in the fishing community as a tool in preventing the disputes in the community. These custom values which include adat laot, hukom adat laot, and hukom meupayong were socialised to the community and applied as the law enforcement effort . These particular effort were used as the main sign carried out by Panglima Laot to prevent conflicts. If the conflicts exist, Panglima laot will solve the conflicts by implementing the customary law which done through Customary Maritime Law Judicial Court.